Criminal Liability for Slander and Article 10 of the European Convention for the Protection of Human Rights and Fundamental Freedoms - R. S. Pelipenko (Путеводитель предпринимателя, 2020)
The purpose of the research is the analysis of the provisions of Russian criminal law concerning slander, as one of the guarantees of constitutional rights to dignity, honor, reputation and good name in the context of the application of the Article 10 of the European Convention on Human Rights and Fundamental Freedoms by the European Court of Human Rights. The quality of the language of the criminal law is important for finding a balance between the mentioned constitutional rights and freedom of speech.